2014
DOI: 10.5056/jnm.2014.20.2.197
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Non-erosive Reflux Disease and High Risk of Obstructive Sleep Apnea in Korean Population

Abstract: Background/AimsObstructive sleep apnea is becoming more important in gastroesophageal reflux disease (GERD) patients. This study investigated the prevalence of high risk for obstructive sleep apnea in GERD patients in comparison with that in healthy controls using the Berlin Questionnaire. We also investigated the risk factors for obstructive sleep apnea in GERD patients. MethodsWe enrolled 1,007 subjects: 776 healthy controls, 115 individuals with erosive reflux disease, and 116 with non-erosive reflux diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 31 publications
(9 reference statements)
0
24
0
1
Order By: Relevance
“…Sleep duration and insomnia may be additional factors affecting the relationship of OSA to sleepiness [6,9]. There is also increasing evidence that medical conditions that often coexist with OSA, such as CRS, anxiety, depression, PTSD and GERD, are associated with sleep complaints [11,12,13,14,15,16,17] and may confound the relationship between OSA and sleep-related quality of life outcomes. The independent contribution of each of these conditions to sleep-related complaints and the associated quality of life has not been closely examined.…”
Section: Introductionmentioning
confidence: 99%
“…Sleep duration and insomnia may be additional factors affecting the relationship of OSA to sleepiness [6,9]. There is also increasing evidence that medical conditions that often coexist with OSA, such as CRS, anxiety, depression, PTSD and GERD, are associated with sleep complaints [11,12,13,14,15,16,17] and may confound the relationship between OSA and sleep-related quality of life outcomes. The independent contribution of each of these conditions to sleep-related complaints and the associated quality of life has not been closely examined.…”
Section: Introductionmentioning
confidence: 99%
“…1,8,16,[93][94][95] Whether extra-esophageal reflux symptoms are truly related to esophageal reflux remains controversial. A recent study has shown that the presence of reflux symptoms is related to significantly higher levels of TRPV1, PAR2, and IL-8.…”
Section: Symptomsmentioning
confidence: 99%
“…The causative relationship between GERD and OSA remains an area of controversy (41). A previous study had shown an association between non-erosive gastroesophageal reflux disease with increased risk of OSA in Korean Population (42). More patients in the GERD group (28.2%) had higher risk for obstructive sleep apnea than healthy controls (20.4%, P = 0.036).…”
Section: Discussionmentioning
confidence: 97%